Understanding the Structural Changes of Lignin Macromolecules From Balsa Wood at Different Growth Stages - Zhang, Chen; Xu, Ling-Hua; Ma, Cheng-Ye; Wang, Han-Min; Zhao, Yuan-Yuan; Wu, Yu-Ying; Wen, Jia-Long (Frontiers in Energy Research, 2020)
Lignin is the most abundant aromatic polymer in nature, that makes it an attractive raw material for producing chemicals, materials, and fuels that are currently obtained from fossil resources. However, the structural complexity, heterogeneity, and variability of the lignin macromolecules hinder the development of eﬃcient valorization technologies for different sources of raw materials. In this study, double enzymatic lignin (DEL) was isolated from different tree-age balsa tree to understand the structural variations of lignin macromolecules during the growth of balsa for the first time. Confocal Raman microscopy (CRM) and component analysis were used to monitor the accumulation of lignin in the plant cell wall. Meanwhile, the structural characteristics and chemical reactivity of DELs were synthetically characterized by advanced NMR techniques. Results showed that the lignin is almost composed of β-O-4 linkages and its content is elevated as the increasing tree-age. Interestingly, carbon-carbon linkages (e.g., β-β and β-5) in these DELs isolated from 3 and 5-year balsa are gradually disappeared. Considering the increasing molecular weight of DELs with the tree-age, it was concluded that lignin macromolecules in balsa wood was gradually polymerized with the increasing growth years. Furthermore, abundant C-O linkages with less C-C linkages in the DELs from 3 and 5-years balsa wood suggested that these feedstocks are promising feedstock in current lignin-first biorefinery scenario. Meanwhile, these lignin fractions from these feedstocks are beneﬁcial to the downstream conversion of lignin into aromatic chemicals. In short, understanding the structural changes of lignin during the growth of balsa wood will facilitate the deconstruction and value-added applications of this kind of feedstock.